Effect of mexiletine on transitory depression of compound motor action potential in recessive myotonia congenita. Issue 2 (February 2015) - Lo Monaco, Mauro; D'Amico, Adele; Luigetti, Marco; Desaphy, Jean-François; Modoni, Anna
Highlights Transient muscle weakness, a frequent symptom of nondystrophic myotonias, can be measured by the transient compound muscle action potential depression. Mexiletine, the currently preferred antimyotonic drug, efficiently reduces the transient compound muscle action potential depression. The 3 Hz prolonged low-rate repetitive nerve stimulation might be considered a helpful tool to objectively assess the anti-myotonic effect of drugs in myotonic patients.